Translating Yi in Hikayat Tiga Negara by using a context-based approach - Oo, Jiu Bell; Goh, Sang Seong (Penerbit Universiti Kebangsaan Malaysia, 2021)
Yi is one of the core philosophical terms in Confucianism with multiple contextual meanings, which has caused problems to translators seeking equivalence in a specific literature. Even though attempts have been made to translate the various meanings of yi from Chinese to English, the translation of yi into Malay remains unchartered. The present study, thus, sets out to interpret and examine the translation of yi in Hikayat Tiga Negara, which is the notable Malay translation of the great Chinese literary masterpiece, San Guo Yan Yi (literally known as The Romance of the Three Kingdoms). Given that the interpretation of yi is contextualized, Shehab and Daragmeh’s (2014) context-based approach to translation is deployed as the theoretical framework. By situating yi in a certain type of discourse (i.e. context of situation), the meaning of yi is interpreted and its translation examined. Subsequently, the translation of yi is discussed following three types of meaning equivalences subsumed under the approach. The findings reveal that yi can be interpreted its meanings by formal equivalence, ideational equivalence, as well as functional equivalence in the forms of literary theme equivalence and interpersonal relationship equivalence, all of which are based on the contextualization cues in its immediate context of use. The study provides meaning equivalences for Chinese-Malay translation of yi. It also highlights the significance of context-based approach to translating the philosophy-infused cultural term.